03.13 Synovial tissue of ra patients in remission contains a unique population of regulatory macrophages. (1st March 2017) - Elmesmari, Aziza; Alivernini, Stefano; Tolusso, Barbara; Vaughan, Diane; Sante, Gabriele Di; Petricca, Luca; Gremese, Elisa; Ferraccioli, Gianfranco; McInnes, Iain B; Kurowska-Stolarska, Mariola
Abstract : Objectives: The majority of RA treatments target inflammation or the adaptive immune response. Partial- or non-response is common and only a minority have sustained remission. There is a knowledge gap in understanding the mechanisms that could reinstate synovial homeostasis in RA. Tissue macrophages may have a role in this process; they are present in healthy synovium and aid resolution of the inflammation in experimental models of RA. However, little is known about the regulatory properties of human synovial tissue macrophages. Our hypothesis is that healthy and RA synovium in remission contain macrophages with anti-inflammatory/repair properties and identifying the effector pathways that drive their function could facilitate therapeutic restoration of synovial homeostasis in RA. Methods and materials: We developed a flow cytometry sorting strategy for harvesting tissue-resident macrophages obtained from digested synovial biopsies of RA patients (n=21, including in remission n=5; and active RA n=16). Cells were labelled with cell lineage specific antibodies; and then macrophages were gated based on their expression of CD64 pos CD11b pos MHCII pos Lineage neg . The potential homeostatic/repair macrophage was preliminary identified by the presence of CD206 marker. CD206 pos and CD206 neg macrophages were sorted using a FACS Aria III and RNAseq preformed to characterise their functional signature. In some experiment, macrophages were seeded on collagen-coated plates and production of TNFα evaluated. Results: All synovial tissue macrophages from RA in remission were CD206 pos whereas a substantial number of synovial macrophages from active RA tissue were CD206 neg . Gene expression analyses and functional assays suggest that these populations represent distinct phenotypes in the activation spectrum. CD206 neg macrophages have high expression of microRNA-155, which drives production of inflammatory mediators eg, TNFα. In contrast, CD206 pos macrophages showed regulatory properties characterised by increased expression of soluble (eg, IL10, TGFB ), surface (eg, IL4/14 R, TGFBR1/2 ) and cellular (eg, SHIP1, TAM, SMAD2, STAT6 ) inhibitors of inflammatory activation, and increased expression of repair markers (eg, ARG2 and CCL18 ). Conclusions: We propose therefore that anti-inflammatory/repair macrophages may be present in human synovial tissues in remission representing a hitherto unnoticed regulatory tissue mechanism.